Ecology - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2003)
Discusses concept of ecology, food chain and also several xamples and activities
Teacher's guide in PDF and Microsoft Word format
System requirements : windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, 640 X 480 resolutions, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC Macintosh at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 MB available RAM, minimum resolution 640 X 480, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Ecology -- Juvenile literature; Ecology